The Russian Financial Crisis and its Consequences for Central Asia - Pastor Campos, Gonzalo; Damjanovic, Tatiana (Washington, D.C. : International Monetary Fund, 2001)
This paper reviews the economic conditions in central Asia at the time of the Russian financial crisis of August 1998; the channels by which the crisis was transmitted to the central Asian region; and the policy responses. The paper concludes that, while real exchange rates of central Asian national currencies vis-a-vis the Russian ruble have returned to their pre-crisis levels following the nominal devaluations that ensued, other indicators of external competitiveness, such as unit labor cost indices, suggest the need for further surveillance in this area. Also, it is not yet clear if full exchange rate flexibility has been established in central Asia despite the protracted and costly exits from the nominal exchange rates in place at the time of the crisis. Finally, the debt-to-GDP ratios in central Asia, which grew rapidly between 1998 and 1999 in the context of large exchange rate adjustments, remain a challenge for the Tajik and Kyrgyz authorities, in particular.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet